2017
DOI: 10.1080/10409238.2017.1287160
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic characteristics of the mitotic chromosome in 1D and 3D

Abstract: While chromatin characteristics in interphase are widely studied, characteristics of mitotic chromatin and their inheritance through mitosis are still poorly understood. During mitosis chromatin undergoes dramatic changes: Transcription stalls, chromatin binding factors leave the chromatin, histone modifications change and chromatin becomes highly condensed. Many key insights into mitotic chromosome state and conformation have come from extensive microscopy studies over the last century. Over the last decade t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 191 publications
(235 reference statements)
0
25
0
Order By: Relevance
“…Closely packed nucleosomes may limit the access of nuclear macromolecular complexes to key sequences, thereby inhibiting transcription 3,4 . Consistent with this idea, repressive nucleosome post-translational modifications (histone marks) are associated with more compact chromatin 4,5 . However, the correlations between transcription, histone marks, and macromolecular packing are poorly understood in situ.…”
Section: Introductionmentioning
confidence: 68%
“…Closely packed nucleosomes may limit the access of nuclear macromolecular complexes to key sequences, thereby inhibiting transcription 3,4 . Consistent with this idea, repressive nucleosome post-translational modifications (histone marks) are associated with more compact chromatin 4,5 . However, the correlations between transcription, histone marks, and macromolecular packing are poorly understood in situ.…”
Section: Introductionmentioning
confidence: 68%
“…Chromatin structure is important for many different cellular functions. A dramatic change in chromatin structure and organization occurs during the transition from interphase to mitosis as the open, diffuse, compartmentalized, and transcriptionally accessible interphase chromatin becomes compact, rod-like, and transcriptionally repressed in mitosis (Wang and Higgins, 2013;Doenecke, 2014;Oomen and Dekker, 2017). While most work studying mitotic chromatin rearrangement focuses on large chromatin-organizing complexes like cohesin, condensin, and topoisomerases (Vagnarelli, 2012), mitosis also is associated with characteristic changes to histone post-translational modifications (PTMs) (Wang and Higgins, 2013;Oomen and Dekker, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Histone PTMs are chemical changes to histones, typically to their tails, some of which are associated with different chromatin structures and densities (Rice and Allis, 2001;Wang and Higgins, 2013). Acetylation, notably of histone 3 lysine 9 (H3K9ac), is associated with euchromatin, which is loosely packed, gene rich, and actively transcribed (Doenecke, 2014) Methylation, notably H3K9me 3 and H3K27me 3 , is associated with heterochromatin, which is densely packed and poorly transcribed (Rice and Allis, 2001;Wang and Higgins, 2013;Oomen and Dekker, 2017). Histone PTMs may also intrinsically alter chromatin packing by changing the charge of histones (acetylation) and introducing hydrophobic moieties to histones (methylation) (Rice and Allis, 2001;Doenecke, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that interphase structures detected by 3C-based methods, such as TADs and compartments, are lost in mitosis (Nagano et al 2017;Gibcus et al 2018;Naumova et al 2013;Oomen and Dekker 2017). However, the resolution of these previous studies was not sufficient to investigate specific looping interactions, e.g.…”
Section: C Shows Loss Of Tads and Ctcf Loops In Prometaphasementioning
confidence: 99%